Symmetrical high voltage gain half-bridge inverter based double-Y-source networks with reduced voltage stress - Hussain Sayed; Oday A Ahmed; Dhari Y Mahmood; Kanaan A. Jalal; Waleed H. Habeeb (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
A single-stage symmetrical high voltage gain half-bridge (HB) DC-AC converter is proposed in this paper. Using two Y-source impedance networks, the following key features are utilized from the proposed topology: single stage inverter with very high voltage gain compared to conventional HB inverter, symmetrical output voltage waveform, low voltage stress across the passive components because it is distributed across two impedance networks, and only two switching devices are needed for the converter. Furthermore, important merit of the proposed topology is that the current drawn by the Y-coupled inductors is symmetrical around the X-axis which helps to prevent the Y-network cores from reaching the saturation state. And the last compelling feature is a virtual neutral point for the load connection is inherited in the proposed double Y-source impedance networks converter with no need for DC-Link capacitors. For low voltage sources such as photovoltaic (PV) and fuel cell, the converter is designed to achieve continuous input current operation. The operation modes and principles of the inverter are analyzed and discussed deeply in this paper. A detailed mathematical equations system is derived and verified for the presented converter. Finally, PSpice simulation tools are used to simulate the converter and verify the derived mathematical formulas.